2005
DOI: 10.1038/sj.cr.7290315
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional characterization of two cDNAs encoding NADPH-dependent 3-ketoacyl-CoA reductased from developing cotton fibers

Abstract: Genes encoding enzymes involved in biosynthesis of very long chain fatty acids were significantly up-regulated during early cotton fiber development. Two cDNAs, GhKCR1 and GhKCR2 encoding putative cotton 3-ketoacyl-CoA reductases that catalyze the second step in fatty acid elongation, were isolated from developing cotton fibers. GhKCR1 and 2 contain open reading frames of 963 bp and 924 bp encoding proteins of 320 and 307 amino acid residues, respectively. Quantatitive RT-PCR analysis showed that both these ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Recombinant ACO1, ACO2, and ACO3 proteins were detected with monoclonal antipolyhistidine antibody (RandD Systems) and visualized after incubating with goat anti-mouse IgG conjugated with horseradish peroxidase (Promega) as previously described (Qin et al, 2005).…”
Section: Yeast Constructs and Aco1-3 Enzyme Activity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant ACO1, ACO2, and ACO3 proteins were detected with monoclonal antipolyhistidine antibody (RandD Systems) and visualized after incubating with goat anti-mouse IgG conjugated with horseradish peroxidase (Promega) as previously described (Qin et al, 2005).…”
Section: Yeast Constructs and Aco1-3 Enzyme Activity Measurementsmentioning
confidence: 99%
“…Parallel reactions using cotton UBQ7 primers were performed to normalize the amount of template cDNA added in each reaction. QRT-PCR was performed using the SYBR Green PCR kit (Applied Biosystems) in a DNA Engine Opticon continuous fluorescence detection system (MJ Research) as previously described (Qin et al, 2005). The QRT-PCR cycles were as follows: initiation with a 10-min denaturation at 958C, followed by 42 cycles of amplification with 10 s of denaturation at 948C, 20 s of annealing according to the melting temperatures provided in Supplemental Table 3 online, 20 to 30 s of extension at 728C, and reading the plate for fluorescence data collection at 78 to 808C.…”
Section: Rt-pcr and Qrt-pcr Analysismentioning
confidence: 99%
“…Interestingly, many cotton genes encoding nonspecific lipid transfer proteins and enzymes involved in various steps during fatty acid chain elongation are highly upregulated during early fiber development (Ji et al, 2003;Qin et al, 2005Qin et al, , 2007Shi et al, 2006;Gou et al, 2007), indicating that the biosynthesis of very-long-chain fatty acids (VLCFAs) or their transport may be required for fiber cell elongation processes. A comprehensive lipid analysis has indicated that linolenic (18:3) and palmitic (16:0) acids are the most abundant fatty acids in developing cotton fibers (Wanjie et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 162 fiber-preferential genes were mapped to 102 metabolic events with ethylene biosynthesis and fatty acid biosynthesis/chain elongation being the most significantly upregulated processes. Systematic studies showed that a large number of genes encoding nonspecific lipid transfer proteins and enzymes that are involved in various steps of fatty acid chain elongation are highly up-regulated during early fiber development, indicating that biosynthesis of saturated verylong-chain fatty acids and/or their transport may also be required for fiber cell growth (3,(7)(8)(9)(10)(11). Exogenously applied lignoceric acid (C24:0) in the ovule culture medium promotes significant fiber cell growth, possibly by activating the transcription of several 1-aminocyclopropane-1-carboxylic acid oxidases involved in ethylene biosynthesis (12).…”
mentioning
confidence: 99%